Socioeconomic inequalities related to dental care needs among adolescents and adults living in the state of Minas Gerais, Brazil - Fabíola Bof de Andrade; Flávia Cristina Drumond Andrade (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2021)
Abstract Background There is significant evidence of inequalities in the need for dental treatment, and their monitoring is essential for public health planning. Objective To measure the extent of the association between socioeconomic inequality and need for dental care. Method This study used data from the 2011 Survey of Oral Health Conditions, including a representative sample of adolescents (n=2,310) and adults (n=1,188) from the state of Minas Gerais, Brazil. Need for dental treatment was evaluated according to criteria of the World Health Organization (WHO). Family income was used as a measure of socioeconomic status. The magnitude of socioeconomic inequalities related to the need for treatment was assessed using the slope index of inequality (SII) and the relative index of inequality (RII). Results Among adolescents, the SII was -22.9% (95% CI -34.8; -11.0) and the estimated RII was 0.61 (95% CI 0.47; 0.79). Among adults, the SII was -28.0% (95% CI -39.8; -16.3) and the RII was 0.58 (95% CI 0.45; 0.74). Conclusion There are socioeconomic inequalities regarding the need for dental treatment, and individuals with lower family income present a higher prevalence of need.